Pengaruh Jumlah Tanggungan Keluarga Terhadap Kemiskinan - Annisa Djafar; Usman Moonti; Boby Rantow Payu; Rosman Ilato; Sudirman Sudirman (State University of Gorontalo, 2023)
The objective of this research was to determine the effect of the number of dependents on poverty in Ayula Selatan Village, Bulango Selatan Subdistrict, Bone Bolango Regency. Morcover, this research employed a quantitative approach with a survey research method. The data used were primary data obtained by distributing questionnaires to the residents of Ayula Utara, Bulango Selatan Subdistrict, Bone Bolango Regency, with a total sample of 70 respondents. At the same time, the data analysis technique used simple linear regression. The finding depicted that there was an effect of the number of dependents on poverty in Ayula Selatan Village, Bulango Selatan Subdistrict, Bone Bolango Regency. The poverty in Ayula Selatan Village, Bulango Selatan District, Bone Bolango Regency was affected by the number dependents for 7.80%, while the remaining 92,20% were affected by other variables that were not examined in this research.